CHIA SEED AS A SOURCE OF IN VITRO ESTABLISHMENT OF Salvia hispanica L. PLANTS - & Salih, Al- Dabagh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Technique of tissue culture for Chia (Salvia hispanica) micropropagation was achieved, this study investigated the impact of various concentrations of plant growth regulators on shoot multiplication and root induction with the Chia’s mature seed as a source explant. The highest percentage of shoot formation (80%), shoots number per explant(3.20) and shoot length(3.26 cm), were recorded on MS medium enriched with BAP(1.0 mgl-1) after eight weeks of seed culture. The optimal medium for the rhizogenesis was achieved on half strength MS medium fortified with 1.0 mgl-1 IBA after four weeks of culture, which had the highest rooting percentage (100%) with highest mean of roots number (5.6 roots per shoot) with (3.40 cm root length). The rooted plants were successfully adapted ex vitro with a survival rate of 85%.